Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Alafenamide in the Treatment of HIV-Infected Patients: Experience with the First 100 Patients from Qatar. (12th August 2020) - Al Soub, Hussam; Al-khal, A. Latif M.; Alsoub, Deema; Awouda, Waleed
Abstract : Background . To describe our experience with the use of Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Alafenamide (EVG/COBI/FTC/TAF) in the treatment of HIV-infected patients in Qatar including both naïve and treatment experienced. We also report the reasons for switching to EVG/COBI/FTC/TAF in treatment-experienced patients, response to treatment, and tolerability. Method . Review of the medical records of the first 100 HIV-infected patients treated with EVG/COBI/FTC/TAF. Results . Among the 100 HIV-infected patients who were treated with EVG/COBI/FTC/TAF, 64 were Qatari and the rest were from other nationalities. 80 patients were males and 20 were females. 29 were treatment naïve, and 71 were treatment experienced. Among treatment-experienced patients, the most common reasons for switch to EVG/COBI/FTC/TAF were safety concerns, followed by regimen simplification and adverse drug reaction of the previous regimen (40%, 14%, and 13%, respectively). Treatment response to EVG/COBI/FTC/TAF leading to undetectable viral load in naïve patients was 69%, and in treatment-experienced patients, it was 83% with an overall response among all patients of 79%. Excluding those who left the country and whose data were not available, the response rate will be 86%. Tolerability was excellent with mild side effects and no discontinuation due to side effects. Conclusion . Experience with the use of EVG/COBI/FTC/TAF in 100 patients with HIV infection in Qatar was favourable both in treatment naïve patients and in those who were treatment experienced with an excellent tolerability.